A Review of The Victimology of Child Abuse - Jumra (Cendekiawan Indonesia Timur, 2023)
This study aims to determine the factors that cause violence against children in Sibulue District, Bone Regency, and the efforts made to overcome violence against children in Sibulue District, Bone Regency. This research was conducted at the Sibulue sector police station. The types of data are primary data and secondary data. Primary data is obtained through direct interviews with respondents who are competent in handling the occurrence of violence against children in Sibulue District, Bone Regency, as well as perpetrators and families of victims of violence against children in Sibulue District, Bone Regency. Secondary data is obtained through literature from various books, legal rules, documents, and other written data related to this research. The results showed the factors causing violent crimes against children in Sibulue District, Bone Regency: the environment, film media, revenge, and the role of the victim/opportunity. Efforts made by the police, especially the Sibulue Sector Police, in tackling crimes of violence against children include preventive efforts (prevention), namely activities that are like directing the community to good things, for example, holding legal counseling, holding KAMTIBMAS lectures, holding lectures related to the role of children in society which include children's NGOs, holding police patrols for security, and other efforts deemed necessary to maintain community security. In addition, there are repressive efforts, namely efforts made after the occurrence of a crime in terms of case disclosure, investigation at the police level to the court level, and punishment carried out in correctional institutions.